Access to mortgage credit and housing price dynamics. Issue 1 (2nd January 2016) - Hui, Eddie C. M.; Ng, Ivan M. H.
ABSTRACT: In real estate studies, arguably the most important topic revolves around what actually affect the price of properties. In addition to various macroeconomic factors, the mortgage industry is also believed to play a major role. Nonetheless, despite its profound implications on the banking sector, the property market, and the economy as a whole, there is no consensus as to the relationship between property price and bank mortgage lending. In light of this, this paper aims to investigate the relationship between property price and mortgage lending, along with other macroeconomic variables, in two housing sub-markets of Hong Kong (i.e. the mass housing market and the luxury housing market). The findings illustrate that one-way directional relationships are discovered 1) from mass housing price to mortgage lending; 2) from luxury housing price to mortgage lending; and 3) from mass housing price to luxury housing price. Macroeconomic factors such as GDP, inflation rate, and interest rate are also found to play a major role in influencing the prices of both property markets and the amount of outstanding mortgage loans. Implications based upon these findings are also discussed.